THE DECISION TO STUDY AT PRIVATE UNIVERSITY IN TANGERANG - BANTEN: THE INFLUENCE OF BRAND IMAGE, QUALITY, PRICE AND TRUST STUDENTS - Mohamad Zein Saleh; Bunga Mawati Ahlia Suci; Alya Syahla; Rizka Alamsaputri (Jurnal Scientia, 2023)
Private Universities (PTS) are currently facing intense competition to get prospective students. The survival of Private Universities (PTS), one of which is supported by the number of students it has. The way that can be done by PTS to get students is to improve its brand image, quality of education, price and trust. This research is to test, analyze and find the direct effect of Brand Image, Quality, Price and Trust on the decision of prospective students to study at private Universities in the Tangerang Region. This study uses a quantitative method by collecting data through online questionnaires for students studying at private Universities in the Greater Tangerang area with a sample of 170. This research adheres to the Structural Equation Modeling (SEM) model and data processing through SMARTPLS 4.0 software. Based on the results of this study, it can be concluded: Brand Image has no effect and is not significant on trust. Product quality has a positive and significant effect on trust. Price has a positive and significant effect on trust. Trust has a positive and significant effect on purchase decision. Brand image has a positive and significant effect on purchase decision. Price has no positive and insignificant effect on purchase decision. Product quality has a positive and significant effect on purchase decision